Educação não formal: conhecendo o que pensam os educadores que atuam nessa modalidade de ensino - Monteiro, Maria Christina Dias (2023)
Non formal education is a field in the educational area. It is represented by diverse intentionally educational actions that take place outside formal schooling such as; environmental studies, visits to museums , educational workshops, social projects amongst others. It is the education that takes place in a great number of different learning ecosystems where the relationship between teaching and learning is estabilished. Most of the time those who work in this educational area are not professionally recognized. The scope of this research is to understand and analyze how the educators that work with non formal education think, in order to discover how they define education, their roles in the process, their needs, facilities and difficulties and to point out paths to initial and continued training, considering that non formal education is very characteristic of Brazil nowadays. This is a qualitative exploratory study and the data collection were carried out in two ways: by drawing up registration forms filled in by educators answering the question “What do you think about education?” and by holding a round of talks to deepen their view on non formal education. The data were analysed from the perspective of “ANDRE, M.: Analise de Prosa, 1983”, an extended alternative to content analysis. The results reveal educational definition from a critical-social perspective as an intentional educational practice, as a process, as an institution and as a product. Educators define themselves as mediators of the teaching and learning process. They are those who teach and have in the environment their greatest ally. They point to the need for a lot of learning, specifc and continued education in order to develop their skills. They don´t feel valued nor recognized by society. In the definition of non formal education educators present concepts that can justify formal education as well. The research raises the question of whether the division between formal and non formal education does make sense, specially concerning the educator´s role in the process as well as the need to use Pedagogy as the science that integrates the phenomenon of education. It also indicates the need for professionalization and a full training of the educators responsible for the learners